MFN Provisions and Related Issues in Bilateral Investment Treaties - MD Atekul, Islam Nur Shuvo (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2025)
MFN provisions have been interpreted in a broad manner allowing the stakeholders to bring in financially beneficial provisions from other BITs. Using this broad interpretation, the policy instrument gives the opportunity to the investor to shop around for suitable provisions of BITs during disputes. The orthodox application provides substantive protection under the forum of international trade law, but in the field of international investment law this provision is used for both substantive and procedural treatment in the area of the investor-state dispute-settlement mechanism. What makes it more challenging is when the investor or the state invokes the investor-state dispute-settlement procedure before a different international settlement forum. Interestingly, the investor and the state earlier agreed on dispute-settlement forums via their BITs, but there are a lot of examples where a state has tried to receive protection from their domestic court in an international matter. Besides, MFN provisions are used for bypassing various requirements for establishing formal international arbitration. So, due to lacunae in government mechanisms, political instability and the lack of knowledge on the BIT’s binding nature, countries have to face legal and economic hurdles after signing it. In this article, the author has tried to discuss this broad interpretation of the MFN provisions of BITs by discussing existing cases of investor-state dispute settlement related to MFN provisions. The author has tried to focus on two basic subjects: a) MFN provisions and related issues regarding investment, and b) MFN provisions and jurisdiction.